The Legal Liability of The Government And Employers In The Exclusive Breastfeeding Program - Lilis Qomariyah Nur Wachidah; Fitriani (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
Breastfeeding is a staple food and the main nutrition source for newborn of 0-6 month old who still can not digest solid food. Exclusive breastfeeding is a process of giving only breastfeeding for the first 6 month old without giving any additional food for baby. The method that was used for this research was normative jurisprudence research, which came from reviewing written law from several aspect and law norms then continued to do research to get a conclusion. From research’s result, it can be concluded that Government Responsibility and Employer in Exclusive Breastfeeding program are the rules that every mother who is working and do the exclusive breastfeeding program should get place for breastfeeding and milk squeezing room (Lactation’s Room). The sanctions that will be given if this thing is being ignored are the employer will get criminal sanction for 1 year and fine for one hundred million rupiahs (Rp. 100.000.000). Therefore in the needs for health improvement, it should be done the Counseling program for whole community about the important of breastfeeding wherever and whenever without exception in office especially for working mothers. In this point the government should confirm that the rule is well done even from monitoring until the sanction is given.